2017
DOI: 10.1038/s41598-017-12232-7
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput targeted screening in triple-negative breast cancer cells identifies Wnt-inhibiting activities in Pacific brittle stars

Abstract: Pro-proliferative oncogenic signaling is one of the hallmarks of cancer. Specific targeting of such signaling pathways is one of the main approaches to modern anti-cancer drug discovery, as opposed to more traditional search for general cytotoxic agents. Natural products, especially from marine sources, represent a largely untapped source of chemical diversity, which so far have mostly been screened for cytotoxicity. Here we present a pioneering pipeline of high-throughput screening of marine-based activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…According to the principles of drug discovery, molecules must have high potential value. Thus, these molecules must be structurally novel and possess pharmacological activity [ 3 , 161 , 162 ]. Information provided in this present review demonstrates the pharmacological activity of components isolated from sea cucumbers.…”
Section: Final Conclusionmentioning
confidence: 99%
“…According to the principles of drug discovery, molecules must have high potential value. Thus, these molecules must be structurally novel and possess pharmacological activity [ 3 , 161 , 162 ]. Information provided in this present review demonstrates the pharmacological activity of components isolated from sea cucumbers.…”
Section: Final Conclusionmentioning
confidence: 99%
“…In our quest to identify novel Wnt-targeting anti-TNBC compounds, we among other approaches screened extracts from deep-sea invertebrates of the Russian Pacific in a set of assays monitoring Wnt signaling in the cancer cells, identifying Ophiura irrorata and other brittle stars collected at the depths of 2.2–3.3 km as a promising source of a powerful anticancer activity [ 7 , 8 ]. Since species collection through deep-sea expeditions necessarily provides a limited material, we decided to investigate whether more easily acquirable Pacific brittle stars could similarly possess interesting anti-TNBC activities.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that starfishes contain steroids, including sterols, polyhydroxysteroids, and saponins remarkably prevented cancer invasion and migration associated with downregulation of matrix metalloproteinase expression. Therefore, saponins could be suggested as an antiinvasive candidate against cancer cells [12][13] . Two polyhydroxysteroids of A. pectinifera starfish were also cytotoxic to the HL-60 cells, with IC 50 values of 80.3 and 40.5 μM.…”
Section: Discussionmentioning
confidence: 99%